2005
DOI: 10.1254/jphs.fp0050613
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of H2-Receptor Activation Against the Duration of Myocardial Hypoxia/Reoxygenation-Induced Ventricular Fibrillation in Sensitized Guinea-Pig Hearts

Abstract: Abstract. Patients with high serum immunoglobulin E levels were reported to be protected against sudden death during acute myocardial infarction. The protection mechanism might be attributed to the facilitation of histamine release from sensitized mast cells; however, this remains to be clarified. In this study, we examined the influence of sensitization on ventricular fibrillation (VF) induced by myocardial hypoxia / reoxygenation (H / R). Guinea pigs were actively sensitized by subcutaneous injection of oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, a role for histamine in the pathogenesis of specific cardiovascular diseases remains controversial. Several studies suggested that histamine could be a negative factor in atherosclerosis (AS) and vascular remodeling, but few studies have directly explored the role of histamine in AMI 10 13 23 24 25 .…”
mentioning
confidence: 99%
“…However, a role for histamine in the pathogenesis of specific cardiovascular diseases remains controversial. Several studies suggested that histamine could be a negative factor in atherosclerosis (AS) and vascular remodeling, but few studies have directly explored the role of histamine in AMI 10 13 23 24 25 .…”
mentioning
confidence: 99%